2010
DOI: 10.5551/jat.4663
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Pioglitazone on Carotid Atherosclerosis in Japanese Patients with Type 2 Diabetes without a Recent History of Macrovascular Morbidity

Abstract: Aim:No previous studies have evaluated the long-term anti-atherosclerotic effects of pioglitazone in Asian patients with type 2 diabetes. Therefore, the present study investigated the protective effects of pioglitazone on the progression of carotid intima-media thickness (IMT), an established surrogate marker of cardiovascular events in Japanese type 2 diabetic patients without a recent history of cardiovascular morbidity. Methods: This 2.5 − 4-year, randomized, open-label, blinded endpoint study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…In contrast, the LDL cholesterol level was the only parameter to show a significant improvement in the non-pioglitazone group. Some of the positive effects of pioglitazone identified in the present study were also previously reported by our group, including the effects on glycated hemoglobin and HDL cholesterol 17) . Other researchers have also reported that pioglitazone therapy results in a significant reduction of systolic blood pressure in type 2 diabetic patients 23) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the LDL cholesterol level was the only parameter to show a significant improvement in the non-pioglitazone group. Some of the positive effects of pioglitazone identified in the present study were also previously reported by our group, including the effects on glycated hemoglobin and HDL cholesterol 17) . Other researchers have also reported that pioglitazone therapy results in a significant reduction of systolic blood pressure in type 2 diabetic patients 23) .…”
Section: Discussionsupporting
confidence: 89%
“…In a recent multicenter study, we reported the effectiveness of pioglitazone in reducing the intimamedia thickness of the common carotid artery in Japanese subjects with type 2 diabetes for up to three years 17) . Based on these results, we designed the present study to examine the effects of pioglitazone on macrovascular diseases (all-cause death, nonfatal cerebral infarction and nonfatal myocardial infarction) in Japanese patients with type 2 diabetes at high risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These three values were averaged. The greatest value among the six averaged IMT values (three from the left and three from the right) was used as the representative value (mean IMT) for each individual [18,19]. For the assessment of carotid artery stiffness, the systolic (Ds) and diastolic (Dd) inside diameter of the bilateral carotid artery were measured approximately 2 cm proximal to the carotid bifurcation at a plaque-free site on M-mode images from recordings made over five cardiac cycles [20].…”
Section: Measurement Of Intima-media Thickness and Stiffness Parametementioning
confidence: 99%
“…The maximal IMT was defined as the greatest axial thickness in the carotid arteries. The mean IMT was calculated as the average of the values of the maximal IMT and two surrounding points on both sides (each 1 cm distant from the point of the maximal IMT) 20) . The mean and maximal IMT values on the side with the highest values were used for the analysis.…”
Section: Measurement Of the Carotid Imtmentioning
confidence: 99%